Expert Testimony in Superior Court, Québec, Case No. 05-04841-72, Chief Robert Kanatewat, et al. vs The James Bay Development Corporation, et al. and The Attorney General of Canada, May 10, 1973. - Feit, Harvey A. (1973)
In the judge’s final ruling he stated that both the part of the corporation witness’ testimony on the effects of development, and my responses were inadmissible so neither could have an effect on his ruling, which was a welcome outcome. Cree and Inuit hunters and their families were the witnesses who convinced the judge to rule that the Project should be stopped while other court cases proceeded. Although the stoppage turned out to be brief it was politically decisive in its impact. I saw my role as providing expert testimony that supplemented what Cree, as unacknowledged experts, were permitted and not permitted to say in court. That their presence and statements were central to the judge’s ruling was clear from his citations of witnesses and his use of some of their terms and concepts in his text. Alongside this, he also cited considerable evidence in support of his conclusions from testimonies of those who were allowed to speak as expert witnesses. This testimony was given in the James Bay Cree’s court case for an interlocutory injection to stop the James Bay Hydro-electric Project construction while other longer court proceedings considered the recognition of their Aboriginal rights. This second time I was asked to give testimony in this case was to respond to the testimonies of expert witnesses called by the Quebec government and its development corporations. As an interlocutory proceeding the focus was on damages that Cree would suffer in the short-term if the Project continued, and whether their damages were greater or lesser than the damages that developers would suffer if the project were temporarily stopped while the proceedings on Cree rights proceeded. This is “expert” witness testimony, even though Cree were clearly the experts. Expert witnesses could testify on what other experts had said and whether it was consistent with what was broadly accepted as knowledge in their disciple of expertise. This testimony reviewed the historical records of the continuity of the long Cree occupation of their ...